SALUTOGENIC EDUCATION OF MENTAL PATIENTS CITIZENS: APPACDM at BRAGA - PORTUGAL - Ana Gomes; Clara Costa Oliveira (Editora da Universidade de Santa Cruz do Sul, 2017)
We present a study of the Portuguese Association of Parents and Friends of Mentally Handicapped Citizens (APPACDM), at Braga - Portugal, aiming to understand how formal and non-formal education of this type of person is salutogenically taken and shared, particularly in terms of space and environment. We proceeded to the Institution's documental analysis, to direct observation and to an interview with the person responsible for the administration of the institution. The data collected are favorable to salutogenesis dimension, although we may refer some critics.